Deaths from cirrhosis in Poland and Hungary: the impact of different alcohol policies during the 1980s. Issue 2 (April 1997) - Varvasovsky, Z; Bain, C; McKee, M
Abstract : OBJECTIVE: To compare patterns of deaths from cirrhosis in Poland and Hungary in the context of differing alcohol policies in the 1980s. DESIGN: Cohort analysis of deaths from chronic liver disease and cirrhosis between 1959 and 1992 using mortality data from the World Health Organization database. RESULTS: The pattern of alcohol related mortality in these countries is quite different. In both countries, death rates increased in the 1960s and 1970s. In Poland, this increase was arrested in 1980 and death rates have levelled out, with the exception of those in young females. In Hungary, rates have continued to climb, although the rate of increase decreased in the 1980s. This change coincides with the introduction of a policy, following the introduction of martial law, to reduce alcohol consumption. CONCLUSIONS: The countries of central and eastern Europe display many similarities in both political history and measures of health such as overall life expectancy. When examined more closely, substantial differences emerge. Policy makers must be cautious about adopting global solutions to health challenges that fail to take into account national variations.